Description of two new micropterous species of Monasavuhygia Brailovsky, 1996 from the Fiji and Solomon Islands and a key to species (Heteroptera: Coreidae: Colpurini) - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2022)
The genus Monasavuhygia Brailovsky, 1996 is revised. Two new species collected in the Fiji Islands and Solomon Islands, respectively, are described in the Tribe Colpurini (Heteroptera: Coreidae). A key to the known species is included, with photographs of the dorsal habitus and female genital plates provided.